Ripartites subtropicus (Paralepistaceae, Agaricales), a newly discovered species from subtropical China - Yang, Yu-Zhi; Deng, Peng-Tao; Yan, Jun; Xiao, Ying-Qun; Zhang, Ping; Chen, Zuo-Hong; He, Zheng-Mi (Phytotaxa, 2025)
Ripartites is a small but globally widespread genus that has rarely been reported before in China. The present study introduces a new species, R. subtropicus from subtropical China, based on morphological and phylogenetic evidence. The phylogenetic analysis based on internal transcribed spacer (ITS) sequences demonstrates that R. subtropicus is close related to R. tricholoma. Ripartites subtropicus differs from other members of the genus by its habitat in northern subtropical high-mountain forests and its predominantly 1- or 2-spored basidia, with fewer occurrences of 4-spored basidia. This species can be distinguished from R. tricholoma also by the lack of hairs on the pileus margin. Additionally, a worldwide key to Ripartites is provided.